#TITLE_ALTERNATIVE# - ALGIFTIAH SYAPDA (NIM : 20111308) PEMBIMBING : Dr. Kuntjoro Adji Sidarto, ZULVA
Investment is an activity that is closely related to the optimization, either to minimize risk or maximize return. One of the best ways for this optimization problems is to determine the proportion of each asset investments. In practice there is condition when the limitations proportions for each asset is exist, this constraint is called a buy-in threshold. The author uses the method of optimization spiral by Tamura and Yasuda (2011) and flower pollination algorithm (FPA) by Yang et al. (2013) for this multimodal problems. Spiral optimization method is specifically converted into a deterministic method using Sobol sequences. As a result, the both metaheuristic methods work favorably in finding solution to optimization problem.